The Efektifitas Polymetric Skipping Terhadap Status Gizi Pada Anak Usia Sekolah Dasar - Yulianita, Marisna Eka; Dewi, Chitra (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Globally, Indonesia is listed as the 5th country with the highest number of children experiencing nutritional problems after India, China, Nigeria and Pakistan. In the current Covid 19 pandemic, social restrictions and physical restrictions have caused school-age children to be closed and caused children to do less physical activity which has an impact on children's energy metabolism. The purpose of this study was to determine the effectiveness of polymetric skipping on the nutritional status of elementary school aged children in Pangkajene Kepulauan Regency. This type of research is a quantitative study, namely Quasy Experiment with a Time Series Design. The data collection process was carried out 2 times a week for 4 weeks. The sample of this research was 31 children of grade 3, 4, and 5 grade which were obtained using purposive sampling technique. The results of statistical tests showed that polymetric skipping had an influence on the nutritional status of elementary school aged children (Ï <0.005). The results of this study also indicated that there was an increase in the value towards the median value based on the age of each child. This means that there is an improvement in the direction of children's nutritional status towards normal nutritional status values. The conclusion of this study is that the provision of this exercise at elementary school age provides a good contribution to children's bone growth.